Self-Regulated Learning Mahasiswa dalam Menghadapi Pembelajaran Daring di Masa Pandemi Covid-19 - M. Yova Syukra (PAKAR Pendidikan, 2022)
AbstractBrave learning has become a new phenomenon in the world of education during the Covid-19 pandemic. Bold learning can affect the learning process to student academic achievement. Students need to have good self-regulation in learning in order to manage their learning strategies well, and improve the quality of their learning. This study aims to determine the level of self-regulated learning in students who are taking courageous learning. This research is a quantitative research with a descriptive survey approach. The subjects in this study were 76 students from the Department of Psychology and PGSD Campus V, Faculty of Education, State University of Padang. The data collection tool uses a Likert scale using a self-regulated learning scale. The data analysis technique used is descriptive statistical analysis. The results of the study indicate that in general the level of self-regulated learning in students who are taking courageous learning is in the medium category.Keywords : self-regulated learning, students